Modifikasi Kunci Algoritma International Data Encryption Algorithm Menggunakan Multiplicative Random Number Generator Untuk Mengamankan Citra Digital - Oktavian Laksamana Suryo; Muhammad Syahrizal; Alwin Fau (STMIK Budi Darma, 2020)
A Digital Image may have important information in it where this confidential information should not be seen by unauthorized people. Information in a digital image can be easily remembered by others compared to information in the form of text. For this reason, images containing information must be encrypted using cryptography, but encoding the image is of course not enough to protect the information contained in it because the key may be known by outsiders.To maintain the confidentiality of information from digital images, digital images will be encoded using the IDEA algorithm, but the level of security of the algorithm should be improved. Therefore, to improve the quality of digital image security, the IDEA algorithm key is first modified using a Multiplicative Random Number Generator.Through the IDEA algorithm process which is quite complicated, coupled with the previously modified key using the Multiplicative Random Number Generator, it is hoped that it can improve the quality of the security of confidential information encoded in a digital image, so that the information contained in the digital image does not leak to it. irresponsible party.Keywords: Digital Image, Modification, Cryptography, IDEA, Multiplicative Random Number Generator.